1968
DOI: 10.1104/pp.43.11.1755
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid-Promoted Lignification and Phenylalanine Ammonia-lyase Activity in a Dwarf Pea (Pisum sativum)

Abstract: Abstract. The effects of gibberellic acid on lignification in seedlings of a dwarf and a tall cultivar of pea (Pisum sativum) grown under red or white light or in the darkness, were studied. Gibberelilic acid (10-6-10-4 M) promoted stem elongation in both light and dark and increased the percentage of lignin in the stems of the light-grown dwarf pea. The gibberellin had no effect oil the lignin content of the tall pea although high concentrations (10-4 M) promoted growth of the itaill plants. Time course studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1969
1969
1981
1981

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We also confirmed this with bean hypocotyl (7). Moreover, many researchers have showed that growth responses of dwarf plants to light differ from those of the tall varieties (1,3,5,11,14,15). These findings suggest a relationship between the dwarf expression and physiological aging of a shoot system.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…We also confirmed this with bean hypocotyl (7). Moreover, many researchers have showed that growth responses of dwarf plants to light differ from those of the tall varieties (1,3,5,11,14,15). These findings suggest a relationship between the dwarf expression and physiological aging of a shoot system.…”
supporting
confidence: 74%
“…We have reported that dwarf expression in the early growth of bean seedlings may be a reflection of a difference in gibberellin content between the tall and dwarf varieties (6,8 (1,3,5,11,14,15). These findings suggest a relationship between the dwarf expression and physiological aging of a shoot system.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Lignification is also correlated with appearance of ammonia-lyase activity (2,16,24). In these situa-1 Supported in part by grant GB 6702 from NSF.…”
mentioning
confidence: 98%
“…L-Phenylalanine ammonia-lyase catalyzes the removal of ammonium ions from L-phenylalanine to yield trans-cinnamate and ammonia (19). Several workers (7,12,28) have demonstrated a GA3-promoted increase of the ammonia-lyase activity in a number of plant species. Since the phenotype of the tomato mutant was suspected to be related to the effects of the gibberellins, it seemed possible that the activity of this enzyme in the yg, would be different from that in the normal.…”
Section: Resultsmentioning
confidence: 99%